Large electrocaloric effect near room temperature in lead–free Bi0.5Na0.5TiO3-based ergodic relaxor observed by differential scanning calorimetry. (October 2019) - Wei, Qiumei; Zhu, Mankang; Zheng, Mupeng; Hou, Yudong; Li, Junjie; Bai, Yang
Abstract: Here, we show the large electrocaloric effect near room temperature in ergodic relaxor (Bi1/2 Na1/2 )0.93 Ba0.07 (Zn1/3 Nb2/3 )0.01 Ti0.99 O3 (BNBZN) observed by a modified differential scanning calorimeter. Microstructure analysis revealed that BNBZN sample demonstrates global pseudocubic structure with locally distorted structures. Electric measurements showed that the sample coexists of two types of polar nanoregions (PNRs) with different coupling ability, and behaves as ergodic relaxor near room temperature. Due to the transition between two types of PNRs around 40 °C, large adiabatic temperature change of 1.04 °C with high electrocaloric strength of 2.1 × 10 −7 °C·m/V was recorded, indicating its promising prospect for solid-state refrigeration application. Graphical abstract: Unlabelled Image